Metal contents in tobacco fields of district Bachok near coastal area of South China Sea. - Tarmizzi, Abdul Hail Ahmad
A simple acid digestion procedure for soil samples has been developed This work is focused on studying the experimental conditions for extracting trace metals from soil sample taken from agriculture land cultivating tobacco crop. The area is located in Bachok, Kelantan. The elements like Cu, Mg, KCu and Zn were quantitatively extracted and determined by AAS. The concentration of these metallic element detennined in soil samples ranged for Cu (0.01 17-0.0S)mg/L, Zn (0.136-0.299)mg/L, Na (3.212-7.212)mg/L, K (1.932-6.957) mg/L and Mg (6.43-1 1.781) mg/L.